The trend-analysis of the psychophysiological indicators in the system of young sportsmen's selection during the stages of their long-time training. - Khoroshukha Mikhail Fedorovich (Kharkov National Pedagogical University, 2011)
The pecularities of the specific effect of the training loads of different direction on the young sportsmen's organism are considered. It's turned out that the specifics of the training process is reflected on the character of changes in the psychophysiological CIC-2 indicator (character of inclination of curve) which is conservative in the most cases. The received changes are of monotipical character. The trend of these changes is determined by the training process direction. The recommendations concerning the selection arrangement are given.